Ranchers Stewardship Alliance: partnering for vibrant prairie communities - Veseth, Dale, author (Colorado State University. Libraries, 2009)
The Ranchers Stewardship Alliance (RSA) is dedicated to educating the community on enhancing our natural resources. One of the major objectives is to train and keep multigenerational ranch families on the land as conservation stewards. These working landscapes will enhance wildlife and resource needs at the lowest cost of any other conservation model. RSA hopes to contribute to vibrant and diverse local communities across the rural landscape.
Presented at the Bridging the gap: collaborative conservation from the ground up conference, September 8-11, 2009, Colorado State University, Fort Collins, Colorado, sponsored by the Center for Collaborative Conservation, https://collaborativeconservation.org/. This conference brought together people with experience working collaboratively to achieve both conservation and livelihood goals in tribal nations, rangelands, forests, watersheds, agricultural lands, and urban areas. The presenter is President of Ranchers Stewardship Alliance.
Keywords: RSA; Ranchers Stewardship Alliance; Matador Ranch Grassbank; rural land conservation